(untitled) - Parra, Viviana Gladys; Aguirre, Marta; Aredes, Ángeles (Universidad Nacional de Cuyo. Facultad de Ciencias Médicas)

Haga su diagnóstico (2010)

(untitled)
Fil: Parra, Viviana Gladys. Hospital Luis Lagomaggiore (Mendoza, Argentina). Servicio de Dermatología